Causes and Characteristics of Traumatic Tympanic Membrane Perforation in a Tertiary Care Hospital - Muhammad Toseef Ijaz, Tarique Ali Shaikh, Aisha Shafiq, Muhammad Ali Khurram Shahzad, Sajid Ali, Khalid Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Due to human violence, perforation of the tympanic membrane is a frequent occurrence all over the world. The abrupt increase in air pressure in the external auditory canal is the pathophysiology of traumatic tympanic membrane perforation. Objective: To assess the causes and characteristics of traumatic Tympanic Membrane perforation in a tertiary care hospital Methodology: The current study was cross sectional study, conducted at the ENT Department of Sahara Medical College Narowal from January 2022 to July 2022. All the patients were examined by a sing ENT specialist and data was recorded on a pre-designed performa. All the analysis of data was done by IBM SPSS version 23. Results: In the current study, totally 80 patients were enrolled. There were 50 (62.5%) male patients while female patients were 30 (37.5%). The mean age in our study was 28 (4.29) years. The most common type of tympanic membrane perforation was slap in 56 (70%) patients followed by blast injury in 8 (10%) patients. On left side of ear, perforation of the Tympanic membrane was observed in 39 (48.75%) patients. Based on number of perforation, single perforation was observed in 72 (90%) patients while multiple perforations were observed in 8 (10%) patients. Conductive hearing loss was observed in 62 (77.5%) patients and Mild Hearing Loss was observed in 44 (55%) patients. Conclusion: Young males, particularly those between the ages of 18 and 30, often have traumatic tympanic membrane perforation. The most frequent cause of traumatic perforation was slap, which affects the left ear more frequently than the right ear. The most common type of hearing loss was conductive, and mild. Keywords: Causes; characteristics; Tympanic Membrane perforation